Combing role of MgO and Al2O3 on viscosity and its correlation to structure of fluorine-free mold fluxes - Wang, Hai-chuan; Bao, Guangda; Sadaf, Shama; Mao, Si-shuo; Wu, Ting (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
By using FactSage calculations, Fourier transform infrared spectroscopy (FTIR), rotational viscometers, and X-ray diffraction (XRD), the combined effect of MgO and Al2O3 on fluorine-free mold flux was confirmed. The viscosity of the slag at 1300 oC decreased with 2-10 wt% MgO, and higher Al2O3 increased the overall viscosity. The trend of the experimental results was consistent with the models of Riboud and Iida, while the FactSage calculation values were relatively higher. The viscosity of the slag was more influenced by the Si-O network than by the Al(B)-O structure and the MgO has a dual effect on the slag structure. The viscosity-temperature curves changed from alkaline to acidic slag characteristics when Al2O3 increased from 8 wt% to 12 wt%, and the trend was not uniform with the addition of 2-10 wt% MgO. Both FactSage calculation and XRD patterns showed that increasing MgO content gradually promoted the growth of Ca3MgSi2O8 and Ca11Si4B2O22 crystals, while the addition of Al2O3 inhibited crystal precipitation.